Transformasi Digital dalam Manajemen Kearsipan Pemerintahan: Implementasi dan Tantangan Sistem Informasi Kearsipan Terintegrasi: Transformasi Arsip Digital - Nur Sahirah Fayruziyah; Ahmad Fauzi; Ali Mustofa (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Digital transformation in archive management has become a strategic necessity to support the effectiveness of administrative governance and the accountability of public organizations in the era of the Fourth Industrial Revolution, including in the education and religious sectors. In response to this demand, the Ministry of Religious Affairs of Sidoarjo Regency has implemented the SRIKANDI application as an integrated dynamic archiving information system. This study aims to analyze the implementation of the SRIKANDI application and identify the challenges encountered in the digital archive transformation process. The research uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research results indicate that the implementation of SRIKANDI significantly improves archive management efficiency, accelerates administrative processes, and strengthens institutional accountability and transparency. Theoretically, these findings contribute to the development of studies in educational management and public administration by emphasizing that the success of digital archive transformation is determined not only by technological aspects but also by organizational readiness, human resource capacity, leadership support, and the cultivation of digital work culture. This study enriches the perspective of information system-based educational management by positioning digital archive management as a strategic instrument in enhancing the quality of governance in government institutions.